Pre-operative spine embolisation for spinal tumors and metastases: 6 years experience at Pusat Perubatan Universiti Kebangsaan Malaysia - Mohd Yaakob, Mohd Naim; Nik Ismail, Nik Azuan; Muda, Ahmad Sobri (Longe Medikal, 2020)
Objective: Our aim is to determine the average intraoperative blood loss in patients who underwent pre-operative spinal tumour embolisation in PPUKM from 2010 until 2016 and to compare with other centres from literature review. Material And Methodology: 15 patients in PPUKM with spinal tumour and spinal metastatic disease underwent pre-operative embolisation before palliative spinal surgery between 2010 and 2016 in PPUKM. Intraoperative blood loss during palliative spinal surgery was documented obtaining the average and median blood loss. Secondary analyses were made on the amount of intraoperative blood loss in comparison to the embolisation materials, degree of embolisation completion, primary malignancy, level of spinal metastatic involvement and total operating time. Result: The average and median intraoperative blood loss during palliative spinal surgery were 1480mls and 1000mls respectively, which is comparable with other centre from literature review. Significant difference is noted in intraoperative blood loss between the different embolisation materials used (P<0.01). 10 patients had complete embolisation and 4 patients had incomplete embolisation with significant difference in terms of blood loss between these 2 groups with P value of <0.01. There was significant positive correlation between operating time and intra-operative blood loss, whereby the longer the operation, the higher the amount of blood loss. Conclusion: The average intraoperative blood loss in patients with pre-operative spinal tumour embolisation in PPUKM is comparable to other centres from literature review thus pre-operative tumour embolisation can reduce perioperative haemorrhage. However, larger study is needed to further analyse correlation between these factors in affecting intraoperative blood loss.